(untitled) (Relegere: Studies in Religion and Reception, 2012)
While "Judeo-Christian" has been used to describe various aspects of American religion, there is scant discussion on how the term has affected the legal definition of religion in the United States. After briefly mapping the various ways the term has been used in Supreme Court opinions, I focus on the Court’s very first use of the term in McGowan v. Maryland, unpacking the working definition of "Judeo-Christian" that is suggested, and tracing how "Judeo-Christian" has influenced the Court’s understanding of religious establishment infringement. I argue that in the McGowan line of Court opinions, the term "Judeo-Christian," while intended to gesture towards religious inclusivity, works instead to support de facto Christian establishment.